Does extended warranty depict competitive advantage to a retailer in a retail-e-tail channel supply chain. (November 2020) - Panda, Shibaji; Modak, Nikunja Mohan; Cárdenas-Barrón, Leopoldo Eduardo
Abstract: For a strong presence of online channel with superior policy traditional brick and mortar channel is losing its footprint rapidly. Under this situation does retail channel survive? To analyze this paper considers a retail-e-tail channel supply chain, where the retailer sells an extended warranty policy purely for its existence given the fierce price competition with the e-tail channel. It is realized that by selling a properly designed extended warranty policy the retailer generates a higher rate of profit margin than the manufacturer. Longer duration of extended warranty at a lower price attracts more customers to buy through the retail channel and hence enhances the retailer's profit margin. Two different coordination contract mechanisms, namely, all unit quantity discount along with franchise fee, and revenue sharing contracts are proposed to resolve channel conflict and asymmetric Nash bargaining product is used for a particular profit split. It revels under any circumstance the retailer denies manufacturer's warranty cost-sharing proposal for a better pay off. Highlights: This paper considers a retail-e-tail channel supply chain. Retailer sells an extended warranty policy given the price competition with the e-tail channel. Retailer generates a higher rate of profit margin than the manufacturer. Longer duration of extended warranty at a lower price attracts more customers to buy. Two different coordination contract mechanisms are proposed to resolve channel conflict.